Analysis and design of class-E power amplifier considering MOSFET nonlinear capacitance - Dat Vuong; Tran The Son; Anh Phan Thi Lan; Hien Dang Quang; Trang Nguyen (Institute of Advanced Engineering and Science, 2022)
Class-E power amplifiers are integrated into many applications because their simple design and high performance. The efficiency of the power amplifier is significantly impacted by the nonlinear characteristic of the switching device, which is not analyzed clearly in theory. The nonlinear drain-to-source parasitic capacitance of the power transistor and the linear external capacitance are both contributed to the optimum conditions for obtaining the exact shunt capacitance. In this paper, a high-efficiency class-E power amplifier with shunt capacitance is designed with the consideration of both linear and nonlinear capacitance. Furthermore, a mathematical analysis is derived to calculate the component values in order to design the class-E power amplifier. Consequently, high power-added efficiency of 94.6% is obtained using MRF9030 MOSFET transistor with parameter of 4W output power and 13.56 MHz operating frequency. Finally, the measurement result of a linear class-E power amplifier circuit is obtained to compare and realize the efficiency of the proposed work.